The Effect of Competence, Compensation and Work Motivation on the Performance of Village Officials in the Ciampel District, Karawang Regency in 2019 - Bambang Setiawan; Sonny Hersona; Edi Suswardji; Dede Jajang Suyaman (At-Tadbir : jurnal ilmiah manajemen, 2022)
Village officials are public service officials who have the duty and responsibility of serving the community in solving all village administrative problems in the Ciampel District, Karawang Regency. This study analyzes the effect of competence, compensation, and work motivation on the performance of village officials in the Ciampel District, Karawang Regency. This research was conducted in the Ciampel District area. The purpose of this study is to obtain empirical evidence and find clarity of phenomena and conclusions about the Effect of Competence, Compensation, and Work Motivation on the Performance of Village Officials in the Ciampel District, Karawang Regency in 2019. This study uses a survey method using primary data obtained from questionnaires. The sample in this study was 85 employees. The data analysis technique used is descriptive quantitative using the path analysis method. This study indicates that the variables of competence, compensation, and work motivation partially have a significant effect on the performance of village officials. While simultaneously, the competency, compensation, and work motivation variables have a significant effect on the performance of the village apparatus.